Awareness of post exposure prophylaxis for human immunodeficiency virus among healthcare professionals in a tertiary care hospital in Telangana, South India - Pandharpurkar, Apoorva; P., Deepak; V., Manjula B. S. (International Journal Of Community Medicine And Public Health, 2022)
Background: India has the third highest number of people living with human immunodeficiency virus (PLHIV) population in the world. Health care personnel (HCP) are major risk group for acquiring HIV infection by accidental occupational exposure. Knowledge on post-exposure prophylaxis (PEP) holds the key to prevent new HIV infections and also helps in reduction of anxiety among HCP in case of accidental exposure. This study was designed to assess the awareness of PEP and to compare the levels of knowledge among various cadres of HCP. Methods: A cross sectional study was conducted on awareness of PEP among the health care personnel of sample size 360 in a tertiary care centre in urban South India. Universal sampling was done and data was collected for a period of three months. Analysis was done using the Epi info 7.2. Results: Knowledge of PEP among HCP was found to be 63.57%. Knowledge of PEP among groups of faculties, post graduate (PG) students, interns, nurses and lab technicians was found to be 73.5%, 70.9%, 62.8%, 56.9% and 42.2% respectively. There was poor knowledge among the most vulnerable groups i.e. nurses and lab technicians who handle the blood samples of number of PLHIV on a given day. There was a felt need among the faculty, PGs and interns for a refresher training every year on advances in HIV prophylaxis and treatment. Conclusions: This study has brought to light the lacunae in awareness of PEP for HIV among HCP. As India has a high prevalence of HIV, and occupational exposure is pretty much inevitable, there is a pressing need to plug the gaps in awareness of PEP.